2020
DOI: 10.1021/acs.jnatprod.9b01128
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Species Account for the Seemingly Idiosyncratic Secondary Metabolism ofSarcophyton glaucumSpecimens Collected in Palau

Abstract: Sarcophyton glaucum is one of the most abundant and chemically studied soft corals with over 100 natural products reported in the literature, primarily cembrane diterpenoids. Yet, wide variation in the chemistry observed from S. glaucum over the past 50 years has led to its reputation as a capricious producer of bioactive metabolites. Recent molecular phylogenetic analysis revealed that S. glaucum is not a single species but a complex of at least seven genetically distinct species not distinguishable using tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…As the marine environment is an important source of bioactive substances, and due to the high chemical diversity and specimen diversity of the Sarcophyton genus [27,28,34,35], it can be expected that new natural products and activities from soft corals of this genus can be continuously discovered in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the marine environment is an important source of bioactive substances, and due to the high chemical diversity and specimen diversity of the Sarcophyton genus [27,28,34,35], it can be expected that new natural products and activities from soft corals of this genus can be continuously discovered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that soft corals of the genus Sarcophyton are important sources of various types of natural products, some of them with notable bioactivies [25][26][27][28]. Our previous chemical study on Sarcophyton cherbonnieri led to the isolation of six new cembranoids cherbonolides A-E and one biscembranoid bischerbolide peroxide, along with a known compound, isosarcophine [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute configurations of 6 , 7 , and analogs have been confirmed in 2019 by Wen et al from the X-ray single crystal diffraction of the same compound 6 , isolated from the soft coral S. trocheliophorum [ 20 ]. Recently, with the development of molecular phylogenetic analysis technology, McFadden et al suggested that S. glacum contained more than seven genetically distinct clades which might be the reason for the continuous discovery of high chemical diversity of secondary metabolites of the soft coral S. glacum [ 38 ]. For the same reason, it is possible that the corals of Sarcophyton genus could generate similar structure biscembranoids as our present study.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that it might not be suitable to place soft coral belonging to the genus Xenia in a single taxon as their morphological characteristics used for traditional taxonomy are not well reflected in the phylogeny in this genus [68]. A recent study from Maloney and McFadden's group suggested that chemical studies in the last 50 years on soft coral Sarcophyton may have unknowingly comprised different cryptic species of Sarcophyton glaucum, leading to apparently distinctive chemical variation [69]. In the future, such studies should be carried out for soft coral Xenia to gain more understanding of their idiosyncratic chemical variation.…”
Section: Discussionmentioning
confidence: 99%